Efficient and high-resolution simulation of pollutant dispersion in complex urban environments by island-based recurrence CFD. (November 2021) - Du, Yaxing; Blocken, Bert; Abbasi, Sanaz; Pirker, Stefan
Abstract: We applied data-based recurrence CFD (rCFD) to model pollutant dispersion in near-field flow configurations. In case of complex topologies, the global-domain version of rCFD fails to account for local recurrent flow features. We therefore developed a novel island-based version of rCFD, which partitions the computational domain to isolate islands of high recurrence prominence, and subsequently defines a distinct recurrence path for each of these islands. We applied island-based rCFD to pollutant dispersion for two side-by-side cubical buildings with three different gap widths in between them and a real urban environment. We showed that numerical predictions of pollutant dispersion by island-based rCFD were in excellent agreement with full CFD simulations, thus outperforming the global-domain version of rCFD. In both applications, island-based rCFD simulations ran three orders of magnitude faster than corresponding full CFD simulations. In the second application, this speed-up enabled real-time simulations on a computational grid of 10 million cells. Graphical abstract: Image 1 Highlights: We developed an island-based version of rCFD to simulate near-field pollutant dispersion in complex urban environments. We applied island-based rCFD to (i) two side-by-side cubical buildings and (ii) a real urban environment. Island-based rCFD simulations agree well with corresponding full LES-based CFD simulations. Island-based rCFD reduces computational times by more than three orders of magnitude.